Blue Light Induces RPE Cell Necroptosis, Which Can Be Inhibited by Minocycline - Song, Weilin; Zhu, Ruilin; Gao, Wenna; Xing, Chen; Yang, Liu (Frontiers in Medicine, 2022)
Purpose: Damage to and death of the retinal pigment epithelium (RPE) are closely related to retinal degeneration. Blue light is a high-energy light that causes RPE damage and triggers inflammatory responses. This study investigates whether blue light induces RPE necroptosis, explores pharmacologic therapy and specific mechanisms, and provides hints for research on retinal degeneration. Methods: The human RPE cell line ARPE-19 was cultured and subjected to blue light insult in vitro. Annexin V/PI was used to evaluate RPE survival. Minocycline was applied to inhibit the death of RPE. Proteomic measurement was used to analyze protein expression. Inhibitors of necroptosis and apoptosis were applied to assess the death mode. Immunofluorescence of protein markers was detected to analyze the mechanism of cell death. Subcellular structural changes were detected by transmission electron microscopy. Reactive oxygen species (ROS) was tested by DCFH-DA. Mitochondrial membrane potential (△ψm) was detected by JC-1. BALB/c mice received bule light exposure, and RPE flatmounts were stained for verification in vivo. Results: Blue light illumination induced RPE death, and minocycline significantly diminished RPE death. Proteomic measurement showed that minocycline effectively mitigated protein hydrolysis and protein synthesis disorders. Necroptosis inhibitors (Nec-1s, GSK-872) increased the survival of RPE cells, but apoptosis inhibitors (Z-VAD-FMK) did not. After blue light illumination, high-mobility group box-1 (HMGB1) was released from the nucleus, receptor-interacting protein kinase 3 (RIPK3) aggregated, and mixed-lineage kinase domain-like protein (MLKL) increased in the RPE. The application of minocycline alleviated the above phenomena. After blue light illumination, RPE cells exhibited necrotic characteristics accompanied by destruction of cell membranes and vacuole formation, but nuclear membranes remained intact. Minocycline improved the morphology of RPE. Blue light increased ROS and decreased △ψm of RPE, minocycline did not reduce ROS but kept △ψm stable. In vivo, HMGB1 release and RIPK3 aggregation appeared in the RPE of BALB/c mice after blue light illumination, and minocycline alleviated this effect. Conclusions: Blue light exposure causes RPE necroptosis. Minocycline reduces the death of RPE by keeping △ψm stable, inhibiting necroptosis, and preventing HMGB1 release. These results provide new ideas for the pathogenesis and treatment of retinal degeneration.